Pengembangan Metode Menulis Puisi Menggunakan Teknik “Atafora” untuk Meningkatkan Kepekaan Siswa terhadap Lingkungan - Elvin Nuril Firdaus; Sony Sukmawan (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2022)
Writing poetry is a person's creative activity in expressing ideas, feelings, and thoughts in written form with a figurative meaning. Poetry writing activities are included in the competence of learning Indonesian. However, a few SMA Negeri 3 Malang students are interested in writing poetry, especially in class X. In addition, the method of writing poetry taught by the teacher is less innovative, so students are less interested. Based on these problems, this study aims to develop a method of writing poetry "Atafora" technique or "Aku Metafora", by combining students' sensory experiences with metaphorical figures of speech. The method used to study is Research & Development (R&D), with validation carried out by experts, practitioners, and limited users. The research was conducted at SMA Negeri 3 Malang. The study's results prove that the "Atafora" technique of writing poetry is considered valid, with a validation score of 80% by poetry experts, 95% by practitioners, and 90% by users. The overall average percentage is 88.33%. Through the development of this method of writing poetry, it is hoped that the interest and ability to write poetry of the students of SMA Negeri 3 Malang will increase.